PENGARUH KOMPETENSI, LOKUS KENDALI (LOCUS OF CONTROL), DAN HUBUNGAN ANTAR MANUSIA (HUMAN RELATION) TERHADAP KINERJA PEGAWAI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA MALANG - Nur Avidah; Dianawati Suryaningtyas; Arien Anjar Puspitosari Suharso (ITB AAS Indonesia Surakarta, 2026)
This study aims to examine the influence of competence, locus of control, and human relation on employee performance at the Population and Civil Registration Office of Malang City. The study used primary quantitative data and employed a census sampling technique with a total of 55 permanent employees. Data were gathered using a Likert scale questionnaire and subsequently analyzed employing multiple linear regression techniques with IBM SPSS version 22. The results showed that, simultaneously and partially, competence, locus of control, and human relation have a positive and significant effect on the employee performance. Furthermore, the findings suggest that employees who possess strong competence and internal locus of control are likely to establish effective human relation, which in turn support overall performance. These outcomes suggest that strengthening these three dimensions can effectively enhance employee performance. For future studies, it is suggested to examine other variables that could potentially affect employee performance in order to develop a more comprehensive analytical framework. Keywords : Competence, Locus of Control, Human Relation, Employee Performance